MENUMBUHKAN MINAT BELAJAR MATEMATIKA ANAK MELALUI PENGAJARAN YANG BERMAKNA DI NAGARI SIMPANG KAPUAK - Nur Rahmi; Edi Saputra; Rahma Oktafia; Wela Lantari; Wina Febriani; Lipi Aprizal (Didaktik : Jurnal Ilmiah PGSD STKIP Subang, 2025)
Mathematics is a fundamental subject that is crucial for developing children's logical and critical thinking skills. However, many elementary school students in rural areas demonstrate low learning interest and struggle to grasp mathematical concepts. The purpose of this study was to describe efforts made to increase children's interest in learning mathematics in Nagari Simpang Kapuak through meaningful instruction. This activity was conducted during a one-month Community Service Program (KKN) with children aged 7 to 9 years. Initial observations, simple lesson planning, daily tutoring using counting quizzes and concrete media (stones, sticks, and buttons), and daily reflections were the implementation methods. The results showed that children were more interested and engaged in learning and had improved basic numeracy skills. Learning delivered in a fun and contextual manner has been shown to overcome initial challenges and improve understanding of mathematical concepts. Previous research emphasizing the importance of concrete media in elementary education supports these findings, which align with the theory of meaningful learning